Robust, Scalable Synthesis of the Bulky Hagfeldt Donor for Dye‐Sensitized Solar Cells. Issue 2 (17th October 2019) - Baumann, Alexandra; Watson, Jonathon; Delcamp, Jared H.
Abstract: The bulky triarylamine group commonly referred to as the "Hagfeldt donor" is a key building block found in many of the organic dyes used in dye‐sensitized applications such as dye‐sensitized solar cells (DSCs). This building block has gained popularity owing to its presence in many of the best‐performing DSC devices reported to date, which use dyes containing this donor group. The Hagfeldt donor provides a desirable 3‐dimensional structure that aids in surface protection of electrons injected into the semiconductor from oxidants in the electrolyte, allowing for record‐setting cobalt‐ and copper‐based redox shuttles to be utilized more frequently. However, the synthesis of this molecule has proven unreliable for many routes. This study concerns a novel, reliable and scalable five‐step synthesis of the Hagfeldt donor. Abstract : We're all going to dye : The bulky triarylamine group commonly referred to as the "Hagfeldt donor" is found in many of the organic dyes used in dye‐sensitized solar cells. However, the synthesis of this molecule has proven unreliable for many routes. This study concerns a novel, reliable and scalable five‐step synthesis of the Hagfeldt donor.